Effect of delays on prognosis in patients with non-small cell lung cancer. Issue 1 (23rd December 2003) - Myrdal, G; Lambe, M; Hillerdal, G; Lamberg, K; Agustsson, Th; Ståhle, E
Abstract : Background: The effect of delay on survival in lung cancer remains uncertain. It is suggested that prompt management of non-small cell lung cancer (NSCLC) can influence prognosis. This study was undertaken to examine the relation between delay and prognosis in patients with NSCLC and to investigate the delay time from first symptom and from first hospital visit to start of treatment. Methods: Two types of delay (symptom to treatment delay and hospital delay) were investigated in 466 patients treated for NSCLC at two institutions in central Sweden. Delays in relation to clinical characteristics were compared and the effects of delay times and other relevant factors on survival were assessed in multivariate analyses. Results: Thirty five per cent of patients received treatment within 4 weeks of the first hospital visit and 52% within 6 weeks. Median symptom to treatment delay was 4.6 months and median hospital delay 1.6 months. Older age, advanced tumour stage, and non-surgical treatment were independently related to poor survival. Both prolonged hospital delay and symptom to treatment delay provided additional information when considered separately. In a final multivariate model only increased symptom to treatment delay gave significant information of a better prognosis. There was an association between a short delay and a poor prognosis which was most pronounced in patients with advanced disease. Conclusion: When considering the whole study population and all stages of tumour together, shorter delay was associated with a poorer prognosis. This is likely to reflect the fact that patients with severe signs and symptoms receive prompt treatment. These findings indicate that the waiting time for treatment in patients with NSCLC is longer than recommended.